Bioaccumulation of tetracycline and degradation products in Lemna gibba L. exposed to secondary effluents - Topal, Murat; Senel, Gulsad Uslu; Obek, Erdal; Topal, E. Isil Arslan (Taylor & Francis Inc, 2016)
The aim of this study was determination of the bioaccumulation capacity of tetracycline (TC) and the degradation products by Lemna gibba L. in the pilot-scale reactor that takes the effluent of a municipal wastewater treatment plant (Elazig city, Turkey). For this aim, L. gibba L. which was exposed to secondary clarifier effluent of the treatment plant was harvested from the pilot-scale reactor. Then, the harvested L. gibba L. was extracted and passed from solid-phase extraction cartridge and TC, 4-epitetracycline (ETC), 4-epianhydrotetracycline (EATC), and anhydrotetracycline (ATC) concentrations were determined. Maximum TC, ETC, EATC, and ATC concentrations bioaccumulated by L. gibba L. were 123 +/- 2.0, 129 +/- 3.2, 42.7 +/- 0.5, and 31.9 +/- 0.3ppb, respectively while minimum TC, ETC, EATC, and ATC concentrations those bioaccumulated by L. gibba L. were determined as 99.7 +/- 1.2, 111 +/- 2.2, 12 +/- 0.6, and 8.3 +/- 0.1ppb, respectively. The order of the uptake rate of TC and the degradation products by L. gibba L. was determined as follows: ETC>TC>EATC>ATC.
Keywords: Treatment; Tetracycline; Lemna gibba L.; LC-MS-MS; Bioaccumulation